Gênero e sexualidade na autoafirmação de juventudes transgressoras em simulação Atheneu ONU: análise pelos princípios da Educação em Direitos Humanos - Morais, Nathália Loyane Fernandes de (2023)
This study aims to analyze, from the perspective of the principles of Human Rights Education (HRE), the process of self-affirmation of transgressive gender and sexuality identities in the Atheneu UN simulation, made possible in the context of the UN Simulation program, developed by high school teachers and students at Centro de Excelência Atheneu Sergipense, a public institution of integral and secondary education that developed the largest UN simulation in Brazil, located in Aracaju/SE. The categories of gender and sexuality are analyzed in an intersectional dialogue (Akotirene, 2019) by decolonial researchers, Lugones (2014); Louro (2014, 2018) and Gomes (2018), and the concept of systemic-inertial racism (Santos, 2022). By transgressing youths in this work are understood as those who break the normativity established by a sociocultural imposition, forged in coloniality as natural, placing in the position of Other the one who opposed the colonial Eurocentric hegemony, by Miranda (2022); Lisbôa (2022); Pires (2022); Medeiros and Nolasco (2022); Lima and Nascimento (2022), and Lelis (2023). Reflecting on the constitution of youths (Pais, 1990), and on their processes of selfassertion, which, diverging in relation to androcentrism and compulsory heterosexuality, are subject to various forms of violence in an educational environment, with consequent damage to their schooling (Abglt, 2016). Faced with this problem, two major premises are assumed: first, that an educational environment guided by the premises of EDH tends to minimize discriminatory situations, including those due to prejudice against sexual and gender diversity and their oppressive intersections (Akotirene, 2019). For promoting, in a transversal way, respect for sexual and gender diversity, and human dignity as legitimate performances of transgressive youths in tune with Human Rights in educational processes, in a post-structuralist perspective through the pedagogy of decolonial transgression, studied by Odara (2020); Miranda (2022); Medeiros, Nolasco (2022); Jesus, Prado (2022), and Pires (2022). Second, HRE occurs, even if implicitly, in UN simulations, since such simulations not only illustrate the functioning of that international organization, but are structured in order to educate for coexistence through dialogue and respectful negotiation, including in conflict situations. This research is based on Foucault’s theory in its critique of heteronormativity and androcentrism that organically compose society (whose culture establishes this sexual pattern as the natural element for affective interpersonal relationships and for the occupation of public and political spaces, regulating them ); and, in this wake, in the ideas of Louro (2013, 2014 and 2018) and Jesus (2013, 2014), in their critique of a universal and essentialist gender identity, and in transgender theory from the perspective of transgender people in their process of selfaffirmation (Brzuzy; Nagoshi; Terrell, 2012), who understand how sociability spaces can act, restricting subjectivities. As specific objectives, firstly, we investigate the school markers that exclude transgressive youths in terms of gender and sexuality in that school; then, it reflects on the potentiality of the UN Simulation as a strategy for education in Human Rights in the school context. With regard to the UN Simulation Program at Atheneu Sergipense, its actions and results are discussed and, in this context, the process of self-assertion of transgressive youths is examined. In view of this, methodologically, the research is developed through two empirical studies whose results are triangulated: in the first, direct observation of the event held at that institution is carried out to identify the main characteristics and dynamics that make up the simulation; in the second, teachers (one of whom is a director of the institution) are interviewed using a semi-structured script; and students (heterosexual, homosexual, bisexual, cisgender, transgender, undefined, non-binary, and others - LGBTI+), who participated in the observed simulation, in order to understand how students perceived their inclusion in the activity and transgressed at school, in their self-affirmation process. The observed data support the content analysis (Bardin, 1977) of the transcribed statements. The results indicate that, despite many contradictions and ambiguities, in an ambivalent relationship with the UN Simulation: in the case of Atheneu UN, I concluded that this was a program that placed the student in a position of protagonism in teaching beyond the learning environment. In it, in 2022, young people proposed their ideas in a space that the school provisionally guaranteed so that, through UN simulations, self-affirmations of transgressive youths in gender and sexualities would occur.